2009
DOI: 10.1007/s00424-009-0672-0
|View full text |Cite
|
Sign up to set email alerts
|

H2O2-mediated modulation of cytosolic signaling and organelle function in rat hippocampus

Abstract: Reactive oxygen species (ROS) released from (dys-)functioning mitochondria contribute to normal and pathophysiological cellular signaling by modulating cytosolic redox state and redox-sensitive proteins. To identify putative redox targets involved in such signaling, we exposed hippocampal neurons to hydrogen peroxide (H 2 O 2 ). Redox-sensitive dyes indicated that externally applied H 2 O 2 may oxidize intracellular targets in cell cultures and acute tissue slices. In cultured neurons, H 2 O 2 (EC 50 118 µM) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 61 publications
3
49
0
3
Order By: Relevance
“…Inhibition of ROS production by vitamin E and Trolox led to a decrease in the Ca 2+ response in astrocytes after activation with ATP, which was dependent on intracellular ER stores. Some other studies have shown that ROS, like H 2 O 2 can affect PLC function by pre-depleting internal Ca 2+ stores (Gerich et al, 2009;Sun et al, 2005;Volk et al, 1997). However, we found a subgroup of astrocytes that did not exhibit H 2 O 2 -induced Ca 2+ signals.…”
Section: Atp-induced Camentioning
confidence: 97%
“…Inhibition of ROS production by vitamin E and Trolox led to a decrease in the Ca 2+ response in astrocytes after activation with ATP, which was dependent on intracellular ER stores. Some other studies have shown that ROS, like H 2 O 2 can affect PLC function by pre-depleting internal Ca 2+ stores (Gerich et al, 2009;Sun et al, 2005;Volk et al, 1997). However, we found a subgroup of astrocytes that did not exhibit H 2 O 2 -induced Ca 2+ signals.…”
Section: Atp-induced Camentioning
confidence: 97%
“…Exposure of hippocampal neurons to subtoxic levels of hydrogen peroxide triggers the release of Ca 2? from the endoplasmic reticulum by causing the opening of both IP 3 and ryanodine receptor channels [143]. Interestingly, superoxide enhances long-term potentiation of synaptic transmission in hippocampal CA1 neurons by a mechanism requiring activation of ryanodine receptors and extracellular regulated kinases [144].…”
Section: Mitostress Versus Mithormesis and Neuroprotectionmentioning
confidence: 99%
“…Evidence has been found for elevated oxidative stress in individuals with DS and in Ts65Dn mice, and a number of genes important for oxidative stress are encoded on HSA21 including SOD1 and RCAN1. Not only may oxidative stress play a role in terms of inducing oxidative damage to proteins, lipids, and nucleic acids, but also reactive oxygen species have been implicated in cellular signaling pathways (Gerich et al 2009). So again, metabolism may be directly related to cellular signaling.…”
Section: Metabolomics and Dsmentioning
confidence: 99%